Partial resection of epithelialized placode without added neurological deficit in myelomeningoceles. Presentation of three cases - Ernesto Enrique Horta-Tamayo; Diana Rosa Ortega-Raez; Lary Benice Rodríguez-Santillán (Acta Médica del Centro)
Introduction: myelomeningocele is the most common form of spinal dysraphism. In the African context, its diagnosis and late surgical treatment are common. Patient information: Three cases of infants diagnosed with myelomeningocele with signs of epithelialization in which the placode was totally or partially resected, without causing an additional defect, are described. The performance of previous imaging studies was conditioned by the lack of availability at the institution and the associated costs. Two cases showed complications (cerebrospinal fluid fistula, surgical wound infection, and post-repair hydrocephalus). Conclusions: Late presentation of patients to specialized centers is a characteristic of surgical treatment of myelomeningocele in low-resource settings. Surgical resection, partial or total, of an exposed and devitalized placode, with signs of epitalization, does not seem to influence the postoperative neurological status.